Features of Anthropometric Indicators of Athletes and Students who do not Play Sports in Men in The Conditions of Karakalpakstan - Utepbergenov A.K; Eshbaev A.J; Sultansuynov A.S. (Zien Journals, 2023)
The article considers the features of somatometric indicators in men engaged in sports in the environmental conditions of the Republic of Karakalpakstan.
Keywords: Physical development; anthropometric indicators; sports; student-athletes